Analysis of clinical outcome and postoperative organ function effects in a propensity‐matched comparison between conventional and minimally invasive mitral valve surgery. Issue 12 (9th September 2020) - Missault, Sophie; Causenbroeck, Jérôme Van; Vandewiele, Korneel; Czapla, Jens; Philipsen, Tine; François, Katrien; Bové, Thierry
Abstract: Background: Minimally invasive mitral valve (MV) surgery (MIVT) is increasingly performed with excellent clinical outcome, despite longer procedural times. This study analyzes clinical outcomes and effects on secondary organ functions in a propensity‐matched comparison with conventional MV surgery. Methods and Results: Out of 439 patients undergoing MV surgery from January 2005 to May 2017, 233 patients were included after propensity‐matching: 90 sternotomy patients and 143 MIVT patients. Endpoints focused on survival, quality of MV repair, and organ function effects through analysis of biomarkers and functional parameters. Regardless of longer cardiopulmonary bypass (sternotomy: 101(IQR33) min—MIVT:143(IQR45) min, p < .001) and cardioplegic arrest times(sternotomy: 64(IQR25) min—MIVT:90(IQR34) min, p < .001), no differences in survival nor complication rate were found. Effect on renal function(creatinine, p = .751 – ureum, p = .538 – glomerular filtration, p = .848), myocardial damage by troponine I level (sternotomy:1.8 ± 3.9 ng/ml – MIVT:1.2 ± 1.3 ng/ml, p = .438) and prolonged ventilatory support >24 h (sternotomy:5.5% – MIVT:8.4%, p = .417) were comparable. The systemic inflammatory reaction by postoperative C‐reactive protein count was markedly lower for MIVT( p < .001). Increased rhadomyolysis was found after MIVT surgery, based on a significant elevation of creatinine‐kinase levels(sternotomy: 431 ± 237 U/L – MIVT: 701 ± 595 U/L, p < .001). Conclusion: Despite an inherent learning curve, minimally invasive MV surgery guarantees a clinical outcome and MV repair quality, at least non‐inferior to those of MV surgery via sternotomy. Notwithstanding longer cardiopulmonary bypass and cardiac arrest times, the impact on secondary organ function is negligible, except for a lower systemic inflammatory response. The postoperative increase of CK‐enzymes suggestive for enhanced rhabdomyolysis needs to be accounted for when procedural times tend to exceed the critical time threshold for severe limb ischemia.